(untitled) (IUBAT Review, 2024)
This study investigates the potential use of rejected heat by outdoor A/C units. Rather from being lost to the environment, the heat will be utilized to make warm water. An experimental setup was designed and constructed that cooled down the refrigerant heat of a condenser by tap water. R22 and tap water were used as hot and cold fluid, respectively. The inlet and outlet temperature of the shell side fluid i.e., water was measured by thermocouple. The mass flow rate of the inlet water was controlled by a valve and measured using a rotameter. The influence of inlet water temperature was also investigated in this study. It is found that recovered thermal energy decreased from 3.72 kW to 2.84 kW as mass flow rate of water decreased from 0.1 kg/s to 0.07 kg/s. When water flow rate decreased to 0.05 kg/s, thermal energy of 4.28 kW was recovered due to the rapid increase of water outlet temperature. Furthermore, this heat exchanger is utilized to determine the heat released by the condenser and the temperature of the condenser-generated hot water. IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 44-63